(untitled) (Jurnal AbdiMas Nusa Mandiri, 2026)
This community service program reports a two-day, project-based workshop on building a profile website with Laravel and the Filament admin panel, followed by publishing to GitHub for vocational high-school students. Objectives were to strengthen industry-relevant CRUD skills and instill version-control practices for portfolio building. The method combined short lectures, live coding, guided hands-on practice, AI-assisted generation of Bootstrap-based HTML for the landing page (via ChatGPT and Gemini), repository publication, and mini presentations. Participants were 66 students across two classes (Day-1 Class A: 32; Day-2 Class B: 34). Data included parallel-form pre/post tests, product rubrics, and satisfaction questionnaires. AI use was limited to landing-page HTML and layout suggestions; outputs were manually curated for accuracy and disclosed in project READMEs. Results show 61/66 students (92.4%) completed a minimal CRUD feature set via Filament Resources and 53/66 (80.3%) published structured repositories with informative READMEs. Average knowledge scores improved from 54 (pre) to 89 (post), yielding a normalized gain of 0.76 (high). Mean satisfaction was 88%. Operational issues on Day 1, uneven software readiness and bandwidth, were mitigated on Day 2 through pre-checks, offline packages, ready-to-run templates, role-based facilitation, and Composer mirrors. The program concludes that the workshop effectively advances vocational competencies in modern PHP web development and produces tangible artifacts (applications and repositories) students can extend and showcase for internships or entry-level opportunities.